Ajaran dan Baiat Ahmadiyah yang Dianggap Menyimpang - Suharmoko Suharmoko (TASAMUH: Jurnal Studi Islam, 2017)
Ahmadiyya sect as a part of religious order is trying to build with the teachings of the Islamic civilization, which has been the most awaited by Muslims, especially Sunnis, the Imam Mahdi. Departing from this paradigm of Imam Mahdi Ahmadi build the base of his community; impose to his people to submit to the central leadership. History of Ahmadiyah in Indonesia was brought by a special messenger of the Ahmadiyah Qadian, namely: Maulana Rahmat Ali, who was sent by the Ahmadiyya Muslim Jamaat, Khalifatul Masih II, Hazrat Mirza Mahmud Ahmad Basyiruddin. Rahmat Ali was charged to convey to Indonesia, that the awaited Imam Mahdi has come into this world. In further development, Ahmadiyah in Indonesia is through the support of Abdul Karim Amarullah, because with his policies, he instructed his students to move in learning Islamic sciences from Egypt to India. Because according to Amarullah, in India the quality of education is not inferior to the quality of education in Egypt. As his students are students who come from Sumatra, Thawalib, are: Abu Bakr Ayyub, Ahmad Zaini Dahlan Din and followed three months later. This article talks about the teaching and understanding of Ahmadiyah in Gambalang